The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0300-483x(00)00181-5
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of oxidative stress in the vanadium-induced cytotoxicity in the MC3T3E1 osteoblast and UMR106 osteosarcoma cell lines

Abstract: The cytotoxicity and free radical production induced by vanadium compounds were investigated in an osteoblast (MC3T3E1) and an osteosarcoma (UMR106) cell lines in culture. Vanadate induced cell toxicity, reactive oxygen species (ROS) formation and thiobarbituric acid reactive substances (TBARS) increased in a concentration-dependent manner (0.1-10 mM) after 4 h. The concentration-response curve of vanadate-induced cytotoxicity and oxidative stress in MC3T3E1 cells was shifted to the left of the UMR106 curve, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
8

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 26 publications
5
97
0
8
Order By: Relevance
“…This result is consistent with previous observations that decavanadate and metavanadate produce different oxidative stress levels in cardiac muscle in toadfish and gilthead seabream (Aureliano et al 2002;Soares et al 2007) and interact differently in vitro with specific proteins such as myosin and sarcoplasmic reticulum Ca 2+ -ATPase (Aureliano and Madeira 1994;Tiago et al 2004;Aureliano and Gândara 2005). Prolonged exposure to low levels of vanadate resulted in an apparent increase in cell viability/number, an effect that was previously observed in mammalian bonederived cell cultures (MC3T3E1 and UMR106) (Barrio et al 1997;Cortizo et al 2000;Etcheverry et al 1997;Salice et al 1999) and attributed to its ability to increase phosphotyrosine protein levels and to inhibit phosphotyrosine phosphatases, thus regulating growth signalling pathways. Although cellular accumulation of metavanadate has been previously demonstrated in mammalian systems, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…This result is consistent with previous observations that decavanadate and metavanadate produce different oxidative stress levels in cardiac muscle in toadfish and gilthead seabream (Aureliano et al 2002;Soares et al 2007) and interact differently in vitro with specific proteins such as myosin and sarcoplasmic reticulum Ca 2+ -ATPase (Aureliano and Madeira 1994;Tiago et al 2004;Aureliano and Gândara 2005). Prolonged exposure to low levels of vanadate resulted in an apparent increase in cell viability/number, an effect that was previously observed in mammalian bonederived cell cultures (MC3T3E1 and UMR106) (Barrio et al 1997;Cortizo et al 2000;Etcheverry et al 1997;Salice et al 1999) and attributed to its ability to increase phosphotyrosine protein levels and to inhibit phosphotyrosine phosphatases, thus regulating growth signalling pathways. Although cellular accumulation of metavanadate has been previously demonstrated in mammalian systems, e.g.…”
Section: Discussionmentioning
confidence: 56%
“…ROS generation was measured by oxidation of DHR to rhodamine as we have previously described (Cortizo, Bruzzone, Molinuevo, & Etcheverry, 2000).…”
Section: Determination Of Reactive Oxygen Species (Ros) Productionmentioning
confidence: 99%
“…6,[13][14][15][16] Studies have been carried out with simple salts and coordination complexes of vanadium in oxidation states III, IV, 6,13,14,16 and V. 6,15,16 In addition to the animal studies, a range of studies was also carried out in several cellular systems, which probed the activity of specific classes of vanadium compounds and how these compounds act. [17][18][19] In such biological studies, the nature of the active vanadium compound cannot readily be identified, and consideration of chemical and metabolic processing is difficult. 6,15,16 However, various approaches to address this problem have provided some further insight as to the biological activity of these compounds.…”
Section: Introductionmentioning
confidence: 99%